A crise de 2008: desregulamentação, inovações e alavancagem financeira das economias capitalistas - Machado, Fabrício Silva de Sousa (2017)
The 2008 crisis allowed Hyman Minsky's theories to be reinserted into the debate on the directions of modern macroeconomics. In a post-Keynesian perspective, this study aims to prove the hypothesis that complex financial innovations, post-Bretton Woods financial market leverage, and deregulation have magnified the fragility and instability of the capitalist economy. Thus, we will treat the causes of the crisis as a problem of theoretical foundation of the capitalist system, because its functioning is based on the deregulation of the financial markets and the dominance of efficient markets hypothesis. Looking at the evidence of the 2008 crisis, it is possible to question the thesis of the new classics that financial liberalization would promote greater efficiency and stability in the system, because with the collapse of US mortgage loans, caused by the proliferation of securitized products, the problem became systemic. This occurs by the amplification of using of off-balance structures such as the shadow bankings, which began in the 1970s, widening the base of the financial capital base outside the control area of the national central bank systems. This situation reinforces the importance of understanding the fundamental dilemma between market deregulation and financial instability, the central object of this work